Patch test results in children and adolescents. Study from the Santa Casa de Belo Horizonte Dermatology Clinic, Brazil, from 2003 to 2010 - Dulcilea Ferraz Rodrigues; Eugênio Marcos Andrade Goulart (Sociedade Brasileira de Dermatologia, 2015)
AbstractBACKGROUND:Patch testing is an efficient method to identify the allergen responsible for allergic contact dermatitis.OBJECTIVE:To evaluate the results of patch tests in children and adolescents comparing these two age groups' results.METHODS:Cross-sectional study to assess patch test results of 125 children and adolescents aged 1-19 years, with suspected allergic contact dermatitis, in a dermatology clinic in Brazil. Two Brazilian standardized series were used.RESULTS:Seventy four (59.2%) patients had "at least one positive reaction" to the patch test. Among these positive tests, 77.0% were deemed relevant. The most frequent allergens were nickel (36.8%), thimerosal (18.4%), tosylamide formaldehyde resin (6.8%), neomycin (6.4%), cobalt (4.0%) and fragrance mix I (4.0%). The most frequent positive tests came from adolescents (p=0.0014) and females (p=0.0002). There was no relevant statistical difference concerning contact sensitizations among patients with or without atopic history. However, there were significant differences regarding sensitization to nickel (p=0.029) and thimerosal (p=0.042) between the two age groups under study, while adolescents were the most affected.CONCLUSION:Nickel and fragrances were the only positive (and relevant) allergens in children. Nickel and tosylamide formaldehyde resin were the most frequent and relevant allergens among adolescents.